The Digital Divide 2.0: Analyzing Connectivity and Device Quality Gaps in Remote Learning - Haruto Takahashi; Luis Santos; Ali Khan (PT. Sinergi Bersahaja Sejahtera, 2026)
Background. The rapid shift to remote learning has intensified concerns about digital inequality, traditionally understood as disparities in access to internet connectivity and devices. Emerging evidence indicates that access alone is insufficient, as differences in connectivity stability and device performance critically shape students’ ability to participate effectively in online learning environments. These developments call for a reconceptualization of inequality within the framework of Digital Divide 2.0. Purpose. This study aims to analyze the impact of connectivity stability and device quality on student engagement and learning effectiveness, and to conceptualize these disparities as multidimensional components of Digital Divide 2.0. Method. A mixed-methods research design was employed involving 312 students from diverse educational contexts. Data were collected through structured surveys, objective connectivity tests, device quality assessments, and qualitative interviews. Quantitative data were analyzed using descriptive and inferential statistics to examine relationships and interaction effects, while qualitative data were analyzed through thematic coding to capture student experiences. Results. The findings indicate that connectivity stability is a strong predictor of student engagement, while device quality significantly influences learning effectiveness. Interaction effects demonstrate that combined limitations in connectivity and device performance produce compounded disadvantages in learning outcomes. Qualitative insights further reveal that students facing unstable connections and low-performing devices experience frustration, reduced participation, and limited access to interactive learning opportunities. Conclusion. Digital inequality in remote learning is multidimensional and extends beyond access to include quality-based disparities in connectivity and devices. Addressing Digital Divide 2.0 requires comprehensive strategies that integrate improvements in digital infrastructure with access to adequate technological resources. Policymakers and educators are encouraged to adopt holistic interventions to ensure equitable and effective remote learning environments.